2008
DOI: 10.1097/mbp.0b013e3282faa732
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of left ventricular systolic and diastolic function by tissue Doppler analysis in patients with hypertension with or without hyperuricemia

Abstract: Mitral inflow velocities and tissue Doppler-derived mitral annular diastolic velocities were significantly different in the patient groups (HT without HU and HT with HU) compared with the control cases. Tissue Doppler-derived myocardial performance index (LV-MPI) was significantly impaired in the patient groups compared with those of the control's (0.48+/-0.09, 0.53+/-0.07, and 0.39+/-0.07, respectively, P<0.001). Significant differences were also observed between the patients who had HT without HU and the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
1
7
0
1
Order By: Relevance
“…Obviously LV MPI was damaged in groups with AH with and without hyperuricemia compared to controls (0.53 ± 0.07, 0.48 ± 0.09, and 0.39 ± 0.07, respectively, p < 0.001). However, it was also observed that the value of LV MPI in patients with AH and hyperuricemia was significantly higher than in patients with AH without hyperuricemia [34]. In our opinion, hyperuricemia can play an important role in the development of diastolic dysfunction in patients with CKD.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Obviously LV MPI was damaged in groups with AH with and without hyperuricemia compared to controls (0.53 ± 0.07, 0.48 ± 0.09, and 0.39 ± 0.07, respectively, p < 0.001). However, it was also observed that the value of LV MPI in patients with AH and hyperuricemia was significantly higher than in patients with AH without hyperuricemia [34]. In our opinion, hyperuricemia can play an important role in the development of diastolic dysfunction in patients with CKD.…”
Section: Discussionmentioning
confidence: 73%
“…They have also found that hyperuricemia can be a marker for subsequent LV dysfunction. The relationship between hyperuricemia and LV dysfunction was evaluated by Tavil Y et al [34]. In this study, the authors assessed the LV myocardial performance index (LV MPI) in tissue Doppler imaging in patients with arterial hypertension (AH) with and without hyperuricemia and a group of healthy control volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…15 Hyperuricemia is also a marker of impaired oxidative metabolism, which may correlate with left ventricular systolic and diastolic dysfunction in patients with chronic heart failure. [16][17][18][19] Heart failure is a state of chronic deterioration of oxidative mechanisms due to enhanced oxidative stress and upregulated oxidant-producing enzymes, in particular xanthine oxidase. This impaired oxidative metabolism may be implicated in the development of cardiac hypertrophy, myocardial fibrosis, left ventricular remodeling, and contractility impairment.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study a positive correlation was observed between UA and EF, (p<0.05 in the presence of obesity). Tavil et al used issue Doppler imaging for the evaluation of myocardial performance index (MPI) (30). MPI in patients with arterial hypertension and hyperuricemia was significantly higher than in hypertensive patients without hyperuricemia.…”
Section: Discussion:-mentioning
confidence: 99%